Strategi Promosi dan Pelestarian Produk Lokal Kopi Sidikalang melalui Pemberdayaan Masyarakat Berbasis Digital dan Kearifan Lokal - Albert Albert; Agus Susanto; Hengky Kosasih; Roseline Roseline; Nasib Nasib (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This Community Service Program aims to increase the capacity of local Sidikalang coffee promotion and preservation through digital technology-based community empowerment and local wisdom values. The activity was carried out in collaboration with farmer groups and coffee MSMEs in Sidikalang District, Dairi Regency, involving 30 participants. The implementation method included digital branding training, social media-based promotional content creation, and a workshop on preserving Sidikalang coffee identity through local cultural narratives. Evaluation was conducted using pretest and posttest instruments to measure participants' understanding of digital promotion strategies and awareness of coffee cultural preservation. The results showed a significant increase in knowledge and skills, with the average participant understanding score increasing from 5.2 to 7.8 out of a total score of 10, an increase of 50%. Participants' interest in utilizing digital platforms for promotion increased from 12 people at the start of the activity to 26 people after the training. In addition, 80% of participants expressed a commitment to maintaining traditional coffee processing practices as part of preservation efforts. The significance test showed a p-value of 0.000 (<0.05), indicating that a digital and local culture-based approach is effective in increasing community capacity in promoting and preserving local Sidikalang coffee products.